Topographic setting of archaeological survey in the Boreal Forest of Alberta - Woywitka, Robin; Michalchuk, Benjamin (My University, 2021)
The archaeological record of the Canadian Boreal Forest is dominated by shallowly buried sites with little to no datable artifacts or stratigraphy. This has led to characterizations of the region as an area of low scientific interpretive value. However, the factors that underlie this skew to shallow sites are rarely formally examined. Here we use a geomorphon-based terrain classification to assess the role of topographic setting in the placement of archaeological survey points. Our results show that there is considerable bias in current archaeological survey methods towards landforms that disperse sediment. This reduces the likelihood of finding deeply buried or stratified sites and calls into question the assertion that datable sites are largely absent from the region. We recommend that increased sampling of low-lying terrain should be a regular component of Boreal Forest survey methodology.
Keywords: Boreal Forest; archaeological survey; geomorphon; topography